The Effect of Flipped Classroom Instruction on Appropriacy of English Apology by Thai EFL Learners - Pornthep Katchamat (International Journal of Pedagogy and Teacher Education, 2018)
Pragmatic competence plays a crucial role in EFL learners’ communicative competence. In order to communicate successfully and appropriately, the effective potential of using pragmatic competence cannot be disregarded. A number of studies have aimed to investigate its production, but how EFL learners acquire and use those production appropriately has not been fully explored. To fulfill this gap, this research article attempted to investigate the effect of the flipped classroom on pragmatic development focused on apology strategies. The participants were 22 English-major students in their third and fourth year of study. The study made use of an experimental design in which the participants were homogenized and taught by the flipped classroom instruction. The data collection was done by using a Discourse Completion Test (DCT) as pre-test and post-test. The findings revealed that the frequency of use in some categories of apology speech act set significantly differed between the two groups, but the overall number of frequency was not significantly different. In addition, the result from the paired sample t-test of the pre-test and post-test showed that the learners who were taught by the flipped classroom instruction used English apology more appropriate and accurate than the pre-test.